Effect of Ultraviolet-C Irradiation on Morphological Character Changes in Patchouli (Pogostemon cablin Benth.) - Haryanti, Sindi; Yusniwati, Yusniwati; Gustian, Gustian (Green Engineering Society, 2024)
Patchouli (Pogostemon cablin Benth.) is among the top 20 essential oil-producing plants traded in the global market. This plant shows narrow genetic diversity due to non-flowering and seed production, increasing the challenges in obtaining new varieties through crossbreeding. Therefore, this research aimed to apply mutation method using ultraviolet-C irradiation combined with tissue culture to broaden the genetic diversity of patchouli. The potential of UV-C irradiation and the morphological changes occurring in the plant were explored from October to December 2023 at the Tissue Culture Laboratory, Andalas University, Padang. In addition, the experiment was arranged in a Randomized Complete Block Design (RCBD) with 10 treatment levels and 3 groups. The treatments included UV-C irradiation doses of 0 (wild type), 30, 60, 90, 120, 150, 180, 210, 240, and 270 minutes at a distance of 30 cm. Data for each patchouli plant per observation variable were presented as mean values, variance, and standard deviation and analyzed using an unpaired t-test. The results showed that exposure to ultraviolet-C radiation impacted several morphological characteristics, such as chlorosis, delayed bud development, increased bud and leaf count, as well as faster bud growth. This phenomenon shows the potential of ultraviolet-C radiation as a physical mutagenic agent.